Spatiotemporal variations and factors associated with surface urban heat islands in South Asia - Linan Sun; Longjue He; Haojie Liu; Peng Kang; Lan Wang; Jvjie Jia; Yuanzheng Li (Urban Climate, 2026)

Cytological and molecular genetic evidence of feminized male gametophyte in the brown alga Saccharina japonica - Xiufeng Zhou; Cailing Yi; Nianchao Xue; Yan Li; Juan Sun; Shuxiu Chen; Yuting Zhai; Liang Shi; Yanling Liu; Nan Zhao; Xia Li; Xiaojie Li; et al. (Algal Research, 2026)

Satellite-derived albedo improves long-term lake energy balance modeling in the central Qinghai-Xizang Plateau - Linan Guo; Wenbin Sun; Yanhong Wu; Jianting Ju; Peizheng Song (Journal of Oceanology and Limnology, 2026)

Inequality in distribution of atmospheric particulate matters and their health exposure risk in Beijing-Tianjin-Hebei, China - Linan Guo; Yuehan Wang; Yi Yang; Yurong Zheng; Li Zhou; Wenbin Sun (Atmospheric Pollution Research, 2026)

AUV path planning method for data collection in underwater wireless sensor network - Zongyu He; Qian Sun; Yibing Li; Linan Ma; Yujie Huang (Ocean Engineering, 2026)

Investigation of hydrate formation and flow characteristics within multiphase transmission pipelines employing a constant pressure visualization loop system - Xi Wang; Kaibang Liu; Shouyi Ma; Linan Guan; Zherui Chen; Yan Qin; Jingyue Sun; Cong Chen (Gas Science and Engineering, 2025)

Homologous nanocellulose modification: A “like cures like” strategy against coffee-ring and infiltration effects in paper-based colorimetric detection - Linan Sun; Yafei Lou; Siyu Chen; Hongyue Weng; Jiahao Li; Zhihui Lin; Junfei Tian; Rong Cao (Analytica Chimica Acta, 2025)

Iron-silicon modified biochar for remediation of cadmium/arsenic co-contaminated paddy fields: Is it possible to kill two birds with one stone? - Han Wu; Linan Liu; Jingmin Sun; Xin He; Zichuan Li; Jingchun Tang (Journal of Hazardous Materials, 2025)

Naturally Occurring Epialleles and Their Roles in Response to Climate Change in Birch - Bowei Chen; Tianxu Zhang; Yile Guo; Lesheng Cao; Xu Zhang; Shahid Ali; Renyi Ma; Linan Xie; Jiang Wang; Gaurav Zinta; Shanwen Sun; Guifeng Liu; et al. (Molecular Ecology, 2025)
Epigenetics has been proposed to be an important mechanism that enables plant species to respond and adapt to environmental and climatic fluctuations and is sometimes entirely uncoupled from genetic variation. Nevertheless, the extent of this uncoupling and the contribution of epigenetics to plant responses to global climate change have not been well studied, particularly in forest trees. Here, we generated a high‐quality genome assembly for Betula platyphylla , a key pioneer species in temperate and boreal forest ecosystems, one of the most sensitive areas to global warming. Extensive multi‐omics sequencing of naturally white birch across the 48 provenances captured their full scope of temperate/boreal forests in Northeast China. Using a genome‐wide association study (GWAS), it was shown that over 55% of differentially methylated regions (DMRs) were spontaneous, independent of genetic factors. More than 30% of the spontaneous DMRs were significantly associated with gene expression, that is, potential epialleles, which are primarily involved in metabolism and responses to abiotic stresses; and 1819 of these epialleles were significantly associated with bio‐climatic variables (i.e., climatic epialleles, cEpialleles). Integrating these cEpialleles into a gradient modelling framework revealed that the natural populations of Asian white birch at high altitude/latitude might be most vulnerable to future climates. Our findings highlight the importance of integrating epigenomic and climatic data sets to forecast the adaptive capacity of a key forest species to rapid climate change.

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Novel amphiphilic magnetic nanocellulose-based phosphotungstic acid type ionic liquid catalysts for biodiesel production - Tao Wang; Yangyang Jiang; Xiqing Wang; Linan Sun; Jingru Zhao; Yujie Fu (Journal of Environmental Chemical Engineering, 2025)

Synthesis of a novel polysaccharide natural functional monomer for imprinted hydrogel microsphere preparation and targeted recognition of anti-tumor drug 7-xylulose-10-deacetylpaclitaxel - Xiaodan Wu; Chengdong Nie; Mengqiong Deng; Linan Sun; Ying Wang; Jingru Zhao; Yujie Fu; Yourong Duan; Ying Sun (Journal of Environmental Chemical Engineering, 2025)

Interface reaction constructs iron and phosphorus functionalized zeolite endowing EP with excellent fire safety and mechanical properties - Qihao Sun; Shanshan Chen; Xiaolong Chen; Linan Dun; Yuanhao Wang (Chemical Engineering Journal, 2025)

Stacking paper sheets into multi-purpose quick response sensing code with built-in nitrocellulose-membrane-free lateral flow assay for detecting tetracycline in food samples - Rong Cao; Yafei Lou; Zhiyuan Yang; Linan Sun; Azadeh Nilghaz; Miaosi Li; Junfei Tian (Food Chemistry, 2025)

Low temperature-mediated changes in soil free-living nitrogen fixation functional groups in tree species at different successional stages in subtropical forests - Feng Sun; Wei Lin; Guangyan Deng; Linan Fan; Hanxia Yu; Zhengchao Yu; Changlian Peng (Plant and Soil, 2025)

Depositional characteristics in the Lower Congo Basin during the Cenomanian-Turonian stage: Insights from fine-grained sedimentary rocks - Bin Zhang; Hongtao Zhu; Xianghua Yang; Zhiwei Zeng; Zhongheng Sun; Linan Pang; Tingting Yao (Marine and Petroleum Geology, 2024)

Climate‐related naturally occurring epimutation and their roles in plant adaptation in A. thaliana - Bowei Chen; Min Wang; Yile Guo; Zihui Zhang; Wei Zhou; Lesheng Cao; Tianxu Zhang; Shahid Ali; Linan Xie; Yuhua Li; Gaurav Zinta; Shanwen Sun; et al. (Molecular Ecology, 2024)
DNA methylation has been proposed to be an important mechanism that allows plants to respond to their environments sometimes entirely uncoupled from genetic variation. To understand the genetic basis, biological functions and climatic relationships of DNA methylation at a population scale in Arabidopsis thaliana , we performed a genome‐wide association analysis with high‐quality single nucleotide polymorphisms (SNPs), and found that ~56% on average, especially in the CHH sequence context (71%), of the differentially methylated regions (DMRs) are not tagged by SNPs. Among them, a total of 3235 DMRs are significantly associated with gene expressions and potentially heritable. 655 of the 3235 DMRs are associated with climatic variables, and we experimentally verified one of them, HEI10 (HUMAN ENHANCER OF CELL INVASION NO.10). Such epigenetic loci could be subjected to natural selection thereby affecting plant adaptation, and would be expected to be an indicator of accessions at risk. We therefore incorporated these climate‐related DMRs into a gradient forest model, and found that the natural A. thaliana accessions in Southern Europe that may be most at risk under future climate change. Our findings highlight the importance of integrating DNA methylation that is independent of genetic variations, and climatic data to predict plants' vulnerability to future climate change.

Apomixis in Saccharina japonica: Parthenogenesis in male and apogamy in female gametophytes - Shutao Yue; Nianchao Xue; Cailing Yi; Juan Sun; Xia Li; Shuxiu Chen; Linan Zhang; Xiaojie Li (Aquaculture, 2024)

Responses of tropical forest soil organic matter pools to shifts in precipitation patterns - Feng Sun; Linan Fan; Guangyan Deng; Yakov Kuzyakov; Yue Zhang; Jinchuang Wang; Yingwen Li; Faming Wang; Zhian Li; Akash Tariq; Jordi Sardans; Josep Penuelas; et al. (Soil Biology and Biochemistry, 2024)

A putative Na+/H+ antiporter BpSOS1 contributes to salt tolerance in birch - Minghui Zhang; Mingke Wu; Tao Xu; Junfeng Cao; Zihui Zhang; Tianxu Zhang; Qingyi Xie; Jiang Wang; Shanwen Sun; Qingzhu Zhang; Renyi Ma; Linan Xie (Plant Science, 2024)

A novel and convenient zeolite modification strategy for enhancing the fire resistance of epoxy resin - Qihao Sun; Linan Dun; Xiaolong Chen; Shanshan Chen; Yuanhao Wang (Chemical Engineering Journal, 2024)

Use of statins and risks of ovarian, uterine, and cervical diseases: a cohort study in the UK Biobank - Xue-Feng Jiao; Hailong Li; Linan Zeng; Huazhen Yang; Yao Hu; Yuanyuan Qu; Wenwen Chen; Yajing Sun; Wei Zhang; Xiaoxi Zeng; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)
Purpose To examine the associations between use of statins and risks of various ovarian, uterine, and cervical diseases, including ovarian cancer, endometrial cancer, cervical cancer, ovarian cyst, polycystic ovarian syndrome, endometriosis, endometrial hyperplasia, endometrial polyp, and cervical polyp. Methods We conducted a cohort study among female participants in the UK Biobank. Information on the use of statins was collected through verbal interview. Outcome information was obtained by linking to national cancer registry data and hospital inpatient data. We used Cox proportional hazards regression to examine the associations. Results A total of 180,855 female participants (18,403 statin users and 162,452 non-users) were included. Use of statins was significantly associated with increased risks of cervical cancer (adjusted hazard ratio (HR), 1.55; 95% confidence interval (95% CI), 1.05–2.30) and polycystic ovarian syndrome (adjusted HR, 4.39; 95% CI, 1.68–11.49). However, we observed no significant association between use of statins and risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial hyperplasia, endometrial polyp, or cervical polyp. Conclusion Our findings suggest that use of statins is associated with increased risks of cervical cancer and polycystic ovarian syndrome, but is not associated with increased or decreased risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial polyp, or cervical polyp.

The tunable synthesis of orange emissive carbon dots for sensitive and selective detection of Hg2+ via portable paper sensor - Yu Gao; Linan Zhou; Zechang Li; Peng Sun; Qijun Dai; Ruifeng Xie; Fang Chai (Journal of Environmental Chemical Engineering, 2024)

An Underwater Triboelectric Biomechanical Energy Harvester to Power the Electronic Tag of Marine Life - Bo Liu; Taili Du; Xiaoyan Xu; Jianhua Liu; Peng Zhu; Linan Guo; Yuanzheng Li; Tianrun Wang; Yongjiu Zou; Hao Wang; Peng Xu; Peiting Sun; et al. (Journal of Marine Science and Engineering, 2023)
Implantable electronic tags are crucial for the conservation of marine biodiversity. However, the power supply associated with these tags remains a significant challenge. In this study, an underwater flexible triboelectric nanogenerator (UF-TENG) was proposed to harvest the biomechanical energy from the movements of marine life, ensuring a consistent power source for the implantable devices. The UF-TENG, which is watertight by the protection of a hydrophobic poly(tetrafluoroethylene) film, consists of high stretchable carbon black-silicone as electrode and silicone as a dielectric material. This innovative design enhances the UF-TENG’s adaptability and biocompatibility with marine organisms. The UF-TENG’s performance was rigorously assessed under various conditions. Experimental data highlight a peak output of 14 V, 0.43 μA and 38 nC, with a peak power of 2.9 μW from only one unit. Notably, its performance exhibited minimal degradation even after three weeks, showing its excellent robustness. Furthermore, the UF-TENG is promising in the self-powered sensing of the environmental parameter and the marine life movement. Finally, a continuous power supply of an underwater temperature is achieved by paralleling UF-TENGs. These findings indicate the broad potential of UF-TENG technology in powering implantable electronic tags.

Spatiotemporal variations, influence factors, and simulation of global cooling degree days - Yuanzheng Li; Tian He; Yuchan Wang; Linan Sun; Yi Yan; Guosong Zhao (Environmental Science and Pollution Research, 2022)

Phytolith evidence for early agriculture in the East Liao River Basin, Northeast China - Jiangyong Wang; Linan Sun; Qi Fang; Jiaxin Fu; Baojian Liu; Ying Liu; Xiangmei Kong; Honghao Niu; Guizai Gao; Meng Meng; Dongmei Jie (Archaeological and Anthropological Sciences, 2021)

Comparative genomic analysis of different virulence strains reveals reasons for the increased virulence of Aeromonas veronii - Bintong Yang; Chong Chen; Yufeng Sun; Linan Cao; Dongxing Zhang; Wuwen Sun; Lei Zhang; Guiqin Wang; Xiaofeng Shan; Yuanhuan Kang; Aidong Qian (Journal of Fish Diseases, 2021)
Aeromonas veronii is an important zoonotic and aquatic agent. More and more cases have shown that it has caused huge economic losses in the aquaculture industry in addition to threatening human health. But the reasons for the increasing virulence of A. veronii are still unclear. In order to further understand the reasons for the increased virulence of A. veronii , we conducted a comparative analysis of the genomes of A. veronii with different virulence. The analysis revealed that there are multiple virulence factors, such as those related to fimbriae, flagella, toxins, iron ion uptake systems and type II, type III and type VI secretion systems in the virulent strain TH0426 genome. And comparative analysis showed that there were two complete type III secretion systems (API1 and API2), of which the API2 and iron ion transport system were unique to the TH0426 strain. In addition, TH0426 strain also has unique functional gene clusters, which may play important roles in terms of resisting infection, adapting to different environments and genetic evolution. These particular virulence factors and gene clusters may be the important reasons for the increased virulence. These insights will provide a reference for the study of the pathogenesis of A. veronii .

Halorubrum depositum sp. nov., a Novel Halophilic Archaeon Isolated from a Salt Deposit - Shaoxing Chen; Siqi Sun; Yao Xu; Jinting Lv; Linan Chen; Liu Liu (Current Microbiology, 2018)

Effects of topography and vegetation on distribution of rare earth elements in calcareous soils - Zhaoliang Song; Yuntao Wu; Xiaomin Yang; Zijuan Xu; Linan Liu; Xiaodong Zhang; Qian Hao; Shaobo Sun; Guilin Han; Congqiang Liu (Acta Geochimica, 2017)

The Functional and Molecular Properties, Physiological Functions, and Pathophysiological Roles of GluN2A in the Central Nervous System - Yongjun Sun; Xiaokun Cheng; Linan Zhang; Jie Hu; You chen; Liying Zhan; Zibin Gao (Molecular Neurobiology, 2017)

Characterization of genome-wide microsatellites of Saccharina japonica based on a preliminary assembly of Illumina sequencing reads - Linan Zhang; Jie Peng; Xiaojie Li; Cuiju Cui; Juan Sun; Guanpin Yang (Journal of Ocean University of China, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Relationship between the velvet-like texture of flower petals and light reflection from epidermal cell surfaces - Yang Zhang; Tianxun Sun; Linan Xie; Takahiro Hayashi; Saneyuki Kawabata; Yuhua Li (Journal of Plant Research, 2015)